Trapped - Anderson, Laurie Halse (Vet volunteers ;, 2009)
Brenna, one of the volunteers at Dr. Mac's Place animal clinic, is horrified to find a dog caught in a trap in the local nature preserve, but subsequent events prove that every story has two sides.